Social Responsiveness, Profitability and Catastrophic Events: Evidence on the Corporate Philanthropic Response to 9/11 - Crampton, William; Patten, Dennis (2008)
In this study we seek to determine whether catastrophic events lead to corporate charitable giving unrelated to levels of firm profitability. We examine the issue relative to the corporate philanthropic response to the 9/11 terrorist attacks of 2001. Based on a sample of 489 Fortune 500 companies, we find that differences in the extent of corporate contributions following 9/11 are positively and significantly associated with differences in firms' profitability. Further, while the degree of connection to the catastrophic event led to higher levels of giving in comparison to the contributions of less connected firms, differences in the extent of philanthropy are still␣related to short-term profitability for the more connected firms. The study thus provides evidence suggesting that even in the wake of catastrophic events, corporate philanthropic giving is constrained by economic concerns.
Keywords: Social Responsiveness; profitability and social performance; Corporate Social Responsibility; Corporate Philanthropy; catastrophic events